Effects of biphasic and monophasic electrical stimulation on mitochondrial dynamics, cell apoptosis, and cell proliferation. Issue 1 (4th August 2018) - Love, Maria R.; Sripetchwandee, Jirapas; Palee, Siripong; Chattipakorn, Siriporn C.; Mower, Morton M.; Chattipakorn, Nipon
Abstract : Currently, electrical stimulation (ES) is used to induce changes in various tissues and cellular processes, but its effects on mitochondrial dynamics and mechanisms are unknown. The aim of this study was to compare the effects of monophasic and biphasic, anodal, and cathodal ES on apoptosis, proliferation, and mitochondrial dynamics in neuroblastoma SH‐SY5Y cells. Cells were cultured and treated with ES. Alamar blue assay was performed to measure cell proliferation. The proteins expression of apoptotic‐related proteins Bcl‐2 associated X (Bax), B cell lymphoma 2 (Bcl‐2), optic‐atrophy‐1 (OPA1), mitofusin2 (Mfn2), phosphorylated dynamin‐related protein 1 at serine 616 (p‐DRP1), and total dynamin‐related protein 1 (Total‐DRP1) were also determined. The results showed that monophasic anodal and biphasic anodal/cathodal (Bi Anod) ES for 1 hr at 125 pulses per minute (2.0 Hz) produced the most significant increase in cell proliferation. In addition, monophasic anodal and Bi Anod ES treated cells displayed a significant increase in the levels of anti‐apoptotic protein Bcl‐2, whereas the Bax levels were not changed. Moreover, the levels of Mfn2 were increased in the cells treated by Bi Anod, and OPA1 was increased by monophasic anodal and Bi Anod ES, indicating increased mitochondrial fusion in these ES‐treated cells. However, the levels of mitochondrial fission indicated by DRP1 remained unchanged compared with non‐stimulated cells. These findings were confirmed through visualization of mitochondria using Mitotracker Deep Red, demonstrating that monophasic anodal and Bi Anod ES could induce pro‐survival effects in SH‐SY5Y cells through increasing cell proliferation and mitochondrial fusion. Future research is needed to validate these findings for the clinical application of monophasic anodal and Bi Anod ES. Abstract : Monophasic anodal and biphasic anodal/cathodal electrical stimulation could induce pro‐survival effects in cells through increasing cell proliferation and mitochondrial fusion.